Pengembangan Perangkat Pembelajaran Problem Based Learning dengan Pendekatan Saintifik untuk Melatihkan Keterampilan Berpikir Kritis Mahasiswa - Adi Candra Kusuma; Dwi Setia Mujiono (JRPM (Jurnal Review Pembelajaran Matematika), 2019)
The research aims to obtain the validity of Problem Based Learning teaching instruments (including lesson plan, textbooks, student worksheets and test for critical thinking skills) through a scientific approach. This type of quantitative research, Quantitative data obtained from the average results of the recapitulation of the validation of experts and colleagues then as an evaluation given through descriptive advice, with the method of collecting observational data, questionnaires and interviews. Data analysis techniques use content and construct validity specified by several experts in the appropriate fields. Construct validation by 2 expert validators and 3 peer validators. The results of the average validation of the learning device recapitulation were obtained RPS (4.00), RPP (4.10), textbooks (4.03), Student Worksheets (4.01) and Tests for students' critical thinking skills (4.00) in the scale range 5 with the title of good to be used as a research instrument. Each of the results of the validation construct of the learning device is given suggestions to be improved before it is used in learning.